2011
DOI: 10.1002/stem.683
|View full text |Cite
|
Sign up to set email alerts
|

Human Induced Pluripotent Stem Cells Harbor Homoplasmic and Heteroplasmic Mitochondrial DNA Mutations While Maintaining Human Embryonic Stem Cell–like Metabolic Reprogramming

Abstract: Human induced pluripotent stem cells (iPSCs) have been recently found to harbor genomic alterations. However, the integrity of mitochondrial DNA (mtDNA) within reprogrammed cells has yet to be investigated. mtDNA mutations occur at a high rate and contribute to the pathology of a number of human disorders. Furthermore, the lack of mtDNA integrity may alter cellular bioenergetics and limit efficient differentiation. We demonstrated previously that the derivation of iPSCs is associated with mitochondrial remodel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(153 citation statements)
references
References 53 publications
9
144
0
Order By: Relevance
“…We found that a rapid bimodal shift toward wild-type or mutant homoplasmy occurred upon reprogramming in MELAS iPSCs, replicating findings of recent reports (40,41). Rapid shifts in mitochondrial heteroplasmy have been observed to occur in germ line (i.e., stem cells) in cows (42,43), in human patients (44,45), in mice with heteroplasmic neutral or potentially pathogenic mtDNA variants (18,25,34), and in primates (46).…”
Section: Discussionsupporting
confidence: 87%
“…We found that a rapid bimodal shift toward wild-type or mutant homoplasmy occurred upon reprogramming in MELAS iPSCs, replicating findings of recent reports (40,41). Rapid shifts in mitochondrial heteroplasmy have been observed to occur in germ line (i.e., stem cells) in cows (42,43), in human patients (44,45), in mice with heteroplasmic neutral or potentially pathogenic mtDNA variants (18,25,34), and in primates (46).…”
Section: Discussionsupporting
confidence: 87%
“…[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Similar to well-recognized genetic and epigenetic factors, OXPHOS-to-glycolysis bioenergetic resetting appears to operate as a crucial enabling regulator of nuclear reprogramming because the self-renewal and pluripotency attributes cannot be efficiently acquired in the presence of an inadequate bioenergetic metabotype. Thus, efficiency of reprogramming is greater the closer the glycolytic/OXPHOS energy metabolism profiles of the starting somatic cells are to those of embryonic stem cells (ESC).…”
Section: Metabolism and Cancer Stemness: Lessons From Ips Cellsmentioning
confidence: 99%
“…Several other excellent examples of the application of quantitative metabolomics in cell culture analysis were presented for the analysis of neuroendocrine cancers and in the analysis of cancer cell metabolic phenotype (Costello et al, 2011). Examples of such analysis include profiling of central metabolism in human cancer cells, identification of metabolic fluxes in hepatic cells (Westra et al, 2011), and several other examples that have been reviewed previously (Prigione et al, 2011).…”
Section: Cancer Cellsmentioning
confidence: 99%